Rancang Bangun Load Balancing Berbasis Mikrotik untuk Meningkatkan Kinerja Akses Internet di Lab Komputer IBN Lampung - Rudi Hartono; Muhammad Putra Pamungkas (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
Reliable and high-performance Internet access is essential to support practical activities in the IBN Lampung Computer Laboratory. Dependence on a single ISP often leads to connection disruptions, reduced service quality, and interruptions in the learning process. This study aims to design and implement a Mikrotik-based load balancing system to improve Internet performance by utilizing two ISP links and providing an automatic failover mechanism when one link becomes unavailable. The research employs the Network Development Life Cycle (NDLC) approach, which includes network requirement analysis, multi-WAN topology design, implementation of load balancing and failover configurations on Mikrotik, and performance testing. The results show that the load balancing system successfully distributes traffic more evenly, enhances connection stability, and provides more consistent Internet speed. Additionally, the failover mechanism works effectively and ensures service continuity when an ISP experiences downtime. In conclusion, the implementation of a Mikrotik-based load balancing system effectively improves Internet access quality and supports smoother laboratory activities.